2015
DOI: 10.1039/c5tc00350d
|View full text |Cite
|
Sign up to set email alerts
|

A low-cost phenylbenzoimidazole containing electron transport material for efficient green phosphorescent and thermally activated delayed fluorescent OLEDs

Abstract: A new electron-transport iTPBI-CN material synthesized through a simple low-cost reaction exhibited a much higher efficiency than commercial TPBI in green OLEDs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(27 citation statements)
references
References 43 publications
0
27
0
Order By: Relevance
“…On the other hand, the ETMs, such as polybenzobisazoles, 25 octasubstituted cyclooctatetraenes (COTs), 26 and quinolinebased materials, 27 exhibit T g 4 200 1C. 30 Shih et al synthesized m-terphenyl oxadiazole derivatives as universal electron-transporting/exciton-blocking materials (T g s B80-105 1C) for phosphorescent OLEDs. 5 Moreover, it has been observed that thermally robust ETMs with T g 4 200 1C give a very stable repeatable performance in OLEDs, whereas the ETMs with T g o 90 1C degrade with high electric field due to the melting/crystallization of the ETM layer.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the ETMs, such as polybenzobisazoles, 25 octasubstituted cyclooctatetraenes (COTs), 26 and quinolinebased materials, 27 exhibit T g 4 200 1C. 30 Shih et al synthesized m-terphenyl oxadiazole derivatives as universal electron-transporting/exciton-blocking materials (T g s B80-105 1C) for phosphorescent OLEDs. 5 Moreover, it has been observed that thermally robust ETMs with T g 4 200 1C give a very stable repeatable performance in OLEDs, whereas the ETMs with T g o 90 1C degrade with high electric field due to the melting/crystallization of the ETM layer.…”
Section: Introductionmentioning
confidence: 99%
“…However, the new compounds of i TPBIPy and i TPyBIPy could be prepared with remarkably high yields over 70% through our previously reported facile one‐step catalyst‐free aromatic nucleophilic substitution reaction by using commercially low‐cost 2,4,6‐trifluorpyridine as electrophiles and 2‐phenyl‐1 H ‐benzo[ d ]imidazole or 2‐(pyridin‐2‐yl)‐1 H ‐benzo[ d ]imidazole as nitrogen nucleophiles at the condition of K 2 CO 3 base and DMSO solvent . It should be noted that by connecting the N‐atom in benzoimidazole to the central phenyl or pyridine in i TPyBIB, i TPBIPy, or i TPyBIPy greatly simplified the synthetic procedures to a single one‐step for the three compounds, which exhibited obvious advantages over the widely reported electron transport material of TPBI or its derivatives with multistep synthetic reactions including the ring‐closing approach of benzoimidazole by linking the C‐atom to the central phenyl ring . Unfortunately, it is unavailable to prepare the isomers of TPBI with N‐linkage in benzoimidazole (1,3,5‐tris(2‐phenyl‐1 H ‐benzo[ d ]imidazol‐1‐yl)benzene, abbreviated as i TPBI) through the same Cu‐catalyzed CN coupling reaction as with i TPyBIB, suggesting the introduction of electron‐withdrawing pyridine in 2‐(pyridin‐2‐yl)‐1 H ‐benzo[ d ]imidazole increased the reactivity of the Ullman reaction.…”
Section: Methodsmentioning
confidence: 99%
“…3, all the compounds exhibited welldefined phosphorescence spectra, which were obtained after dissolving them in 2-methyl-tetrahydrofuran (2-MeTHF) at 77 K. In the phosphorescence spectra, the vibronic sub-band with the highest energy represented triplet energies (E T ) of 1À4 were observed; 2.71, 2.69, 2.66, and 2.65 eV for 1, 2, 3, and 4, respectively. The triplet energies of 1À4 are higher than carbon-based compound, TPBi (ET ¼ 2.63 eV) [24], which indicates that silicon atom effectively breaks the conjugation and attenuates the triplet wave function. Furthermore, the triplet energy levels of compounds were sufficiently higher than that of Ir(ppy) 3 , a phosphorescent dopant that emits green light.…”
Section: Photophysical Propertiesmentioning
confidence: 99%
“…Compounds 2 and 3 have excellent thermal stability, which could be ascribed to the increase in their molecular size. In particular, the compound 3 showed higher thermal stability compared with carbon-based DBI compound, TPBi (2-[3,5-bis(1-phenylbenzimidazol-2-yl)phenyl]-1-phenylbenzimidazole, T g ¼ 124 C) [24], and this higher T g value of compound 3 would gave advantages for the high morphologic stability of the amorphous phase in a deposited film, which is a prerequisite for applications in OLEDs.…”
Section: Thermal Analysismentioning
confidence: 99%